ECONOMIC EFFICIENCY OF SHORT-ROTATION CROP SUCCESSION DEPENDING ON SUGAR BEET FERTILIZATION SYSTEM - Tyshchenko, M. V.; Filonenko, S. V.; Borovyk, I. V.; Koval, O. V.; Hudymenko, Zh. V. (Scientific Progress & Innovations, 2020)
Applying mineral and organic fertilizers under sugar beet is one among important measures of raising the level of economic efficiency of grain and beetroot crop rotations. However, there are not enough experimental data concerning the effect of fertilization system of sugar beet and other crops cultivated in the zone of insufficient moistening on economic efficiency of short-term rotation crop succession. So, these are the topicality and practical importance of corresponding studies, the aim of which is to determine the effect of fertilizing sugar beet and other crops on economic efficiency of short-term rotation crop succession. The task of the research was to study the influence of various fertilization systems used during cultivating sugar beet and other crops in short-term rotation crop succession, on different economic indicators, characterizing the efficiency of agricultural production; to choose the best variant of fertilizing sugar beet and other crops concerning economic characteristics. Corresponding experiments were conducted in the Left-Bank Forest- Steppe of Ukraine, during long-term permanent experiment in the structural subdivision of the Institute of Bio-Energy Crops and Sugar Beet of the National Academy of Agrarian Sciences of Ukraine, at Veselyi Podil Experimental Selection Station (in Semenivka district, Poltava region) during 2015–2018. As a result of the studies, it has been established that in short-rotation crop succession, applying 6.25 t of manure + N56.2Р75.0К56.2 and 12.5 t of manure + N33.8Р45.0К33.8 per 1 ha of plow land during crop rotation resulted in the highest gross output value – 19,166 and 19,270 UAH, respectively. Applying 6.25 t of manure + N11.2Р15.0К11.2 and 6.25 t of manure + N33.8Р45.0К33.8 during crop rotation ensured obtaining the highest net operating profit per 1 ha of crop rotation area – 9,728 and 8,569 UAH, respectively. Among various fertilizers’ doses, the best profitability was achieved at applying 6.25 t of manure + N11.2Р15.0К11.2 and 6.25 t of manure + N33.8Р45.0К33.8 – 108 and 82 %, respectively, per 1 ha of rotation area during crop succession.